Autonomy support and control within mother-father parenting structures: A person-centered approach in youth sport. (March 2021) - O'Neil, Liam; Amorose, Anthony J.
Abstract: In the youth sport context, parents play an important role in the motivation of adolescent athletes. From a self-determination theory viewpoint, the provision of autonomy support versus control by parents is an essential part of this socialization process. The purpose of the present study was threefold: (a) identify distinct mother-father parenting profiles of autonomy support and control based on perceptions of adolescent athletes, (b) examine the unique influence of mother-father parenting profiles on adolescent athletes' motivational responses (i.e., parent-to-child effects), and (c) understand the contribution of adolescent athletes' motivation to the emergence of these mother-father parenting profiles (i.e., child-to-parent effects). To test our hypotheses, a person-centered approach (latent profile analysis) was employed to analyze data collected from a sample of high school athletes ( N = 264; Mage = 15.7 years, 64% female). Results provided evidence supporting a four-profile solution: Strong Autonomy Support Dominant: Both Parents ( n = 26, 9.8%), Weak Control Dominant: Both Parents ( n = 111, 42.0%), Moderate Autonomy Support and Control: Both Parents ( n = 21, 8.0%), and Weak Autonomy Support Dominant: Both Parents ( n = 106, 40.2%). The four mother-father parenting profiles were found to be differentially predicted by, and predictive of, adolescent athletes' adaptive and maladaptive motivational responses (i.e., basic psychological needs satisfaction, autonomous and controlled motivation). This study illuminated a general pattern of congruency in the provision of autonomy support and control by parents within mother-father parenting structures and contributed empirical evidence pointing to the reciprocal nature of interpersonal processes in parent-athlete relationships. Highlights: Investigated mother-father parenting units' provision of autonomy support and control in youth sport. Four parenting profiles were identified with unique patterns of autonomy support and control. All parenting profiles demonstrated congruency in mother's and father's parenting styles. Parenting profiles characterized by autonomy support dominant patterns were optimal for athlete motivation. Athlete autonomous motivation linked to membership in more autonomy-supportive parenting profiles.